Progress and Challenges in China Turfgrass Abiotic Stress Resistance Research - Jiuxin, Lai; Liebao, Han (Frontiers in Plant Science, 2022)
Turfgrasses are an important vehicle for urban ecology and one of the most important indicators of economy and civilization. The biological characteristics of different turfgrass species affect the productivity and quality of the turf and its potential use in landscapes, slopes, and sports fields. Cultivation and management techniques can assist turfgrasses to meet the challenges of climate change, while the development of molecular breeding will provide a broader platform for the application of turfgrasses. The turfgrass industry of China has developed considerably in the last three decades; however, there is still an objective gap with developed countries. This manuscript reviewed the research progress of turfgrass resistance breeding, analysed the bottlenecks in the development of turfgrass resistance breeding, and put forward the strategies to cope with the bottlenecks. Our review aims to promote research and utilization of turfgrasses.